Role of Graphite in Cast Iron on Tribological Behavior in Nano-Scratch Test - Ryuta NAKAMURA; Akira IWABUCHI (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2012)
In previous study, the role of graphite on tribological behavior of cast iron was examined, and the model of cast iron in wear mechanism was proposed. However, this wear mechanism is the model for macro scale test, and has the possibility of showing behavior different from the model shown by the macro scale test in micro-nano scale test. Then, in this study, nano scratch test was carried out by using cast iron and S45C steel as a comparison, it aimed to examine role of graphite in cast iron for the micro-nano scale. As a result, it was understood that the model shown in the macro scale test was the same in micro-nano scale test. And in micro-nano scale, it thought that formation and maintenance of graphite film were dependent on the stick slip phenomenon by increase in indentation depth accompanying increase in load.